2021
DOI: 10.1108/jaar-09-2020-0194
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility, firm value and life cycle: evidence from Southeast Asian countries

Abstract: PurposeThis study extends related research on corporate social responsibility (CSR) into the less-researched realm of Southeast Asia setting by investigating the role of life cycle stages on the relationship between CSR and firm value.Design/methodology/approachThis study uses a sample of 1,247 firm-year observations of firms listed in Southeast Asia from 2012 to 2018. Descriptive, multiple regression and sensitivity analyses are presented in the study.FindingsThe results provide evidence that although CSR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 61 publications
3
26
1
11
Order By: Relevance
“…The findings of this study strengthen the studies conducted by Servaes and Tamayo (2013);Astuti et al (2018); Laili et al (2019); Amato and Falivena (2019); Seok et al (2019); Kamaliah (2020); Hendratama and Huang (2021) which concluded that CSR disclosure promotes better firm value, indicating that the more social disclosure items and the better the quality of the disclosure, the greater the firms' value.…”
Section: Discussionsupporting
confidence: 87%
“…The findings of this study strengthen the studies conducted by Servaes and Tamayo (2013);Astuti et al (2018); Laili et al (2019); Amato and Falivena (2019); Seok et al (2019); Kamaliah (2020); Hendratama and Huang (2021) which concluded that CSR disclosure promotes better firm value, indicating that the more social disclosure items and the better the quality of the disclosure, the greater the firms' value.…”
Section: Discussionsupporting
confidence: 87%
“…Following Hendratama and Huang (2021), we use Dickinson's (2011) classification to classify firms under the high (low) life cycle stage. Dickinson (2011) identified mature (introductory) firms as high (low) stage firms.…”
Section: Methodsmentioning
confidence: 99%
“…The fifth prominent theme unearthed through empirical investigation is corporate sustainability, encompassing socially responsible practices. Corporate social responsibility (CSR) in this context zeroes in on practices that not only meet legal requirements and foster local community development but also safeguard the needs of future generations (Hendratama & Huang, 2021). Notably, across all case studies, Best Practice Corporations have exhibited a myriad of actions aimed at bolstering their sustainable performance in governance, societal impact, and environmental stewardship, as depicted in Table 7.…”
Section: Resultsmentioning
confidence: 99%